Neonatal outcome with 0ral versus Vaginal Misoprostol for Labour Induction - Sultana, Nadira; Saha, Dipa; Begum, Marium; Yeasmin, Sabiha; Alam, Khairul; Akhter, Arifa; Hasin, Wahida (Northern International Medical College Journal, 2017)
Background : Misoprostol is being used widely through different routes for induction of labour. Neonatal outcome may be different with using different routes. Objective : To see the neonatal outcome for induction of labour by misoprostol in oral versus vaginal route. Materials and Methods : This prospective and comparative study was carried out in the dept. of Obstetrics and Gynecology of Jalalabad Ragib- Rabeya Medical College and Hospital, Sylhetfrom July 2008 to June 2009.A total 200 pregnant women completed 28 weeks pregnancy upto 42 weeks were selected for the study.Out of which 100 pregnant women were includedin oral misoprostol group and 100 in vaginal misoprostol groupby simple randomization. Inclusion criteria were single live fetus with cephalic presentation, normal fetal heart rate, adequate pelvis and Bishop score <5. Exclusion criteria were previous uterine scar, estimated fetal weight >4 kg, parity more than 3 and history of hypersensitivity to misoprostol. Neonatal outcome in terms of Apgar Score, passage of meconium, perinatal depression and admission to Neonatal Intensive Care Unit (NICU) compared between two groups. Results : Most of the neonate in vaginal group had low Apgar score. Two percent neonate had Apgar score 2 and 86% had 4-6 in 1 minute in vaginal group whereas in oral group it was 4-6 in 88%.Perinatal depression more in vaginal group 18(18%) than oral group 8(8%). More neonate need admission to Neonatal Intensive Care Unit (NICU) in vaginal group 4(4%) than oral group 2(2%). Only 1% neonate passed meconium in vaginal group. Conclusion : This study concluded that neonatal outcome was better and safe with oral misoprostol than vaginal route. Northern International Medical College Journal Vol.8(2) January 2017: 228-230